ANALYSIS OF THE EFFECT OF FOREIGN DIRECT INVESTMENT ON ECONOMIC GROWTH: THE CASE OF GHANA - Umar Gingo, Halima; Demireli, Erhan (International Journal of Contemporary Economics and Administrative Sciences, 2018)
This paper analyzes the effect of foreign direct investment in a typical developing economy: Ghana, for the period 1980-2015. The Vector Error Correction Model (VECM) results show that foreign direct investment has a negative and statistically significant effect on economic growth. The result seem to support the argument that foreign direct investment into the industrial sector might not be growth enhancing. In addition the results showed that trade openness had a negative and statisticlly significant effect on economic growth. Gross Domestic Investment and the human capital proxy were found to have a positive, though, statistically insignificant effect on growth. Gross Fixed Capital formation was also found to have a negative and statistically insignificant effect on economic growth. To investigate the long run equilibrium relationship, Johansen and Juselius co-integration approach is used, while the speed of adjustment in the short run is analyzed through the use of Vector Error Correction Method (VECM) method. In order to check for the direction of causality between the two variables, the Toda Yamamoto Granger causality test is applied. The results indicate that foreign direct investment has a negative effect on economic growth in Ghana in the long run.